2015
DOI: 10.3390/soc5010187
|View full text |Cite
|
Sign up to set email alerts
|

Towards Sustaining Levels of Reflective Learning: How Do Transformational Leadership, Task Interdependence, and Self-Efficacy Shape Teacher Learning in Schools?

Abstract: Abstract:Whereas cross-sectional research has shown that transformational leadership, task interdependence, and self-efficacy are positively related to teachers' engagement in reflective learning activities, the causal direction of these relations needs further inquiry. At the same time, individual teacher learning might play a mutual role in strengthening school-level capacity for sustained improvement. Building on previous research, this longitudinal study therefore examines how transformational leadership, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 100 publications
2
27
0
Order By: Relevance
“…Stajkovic and Luthans (1998) meta-analysis, which focuses on professional performances, shows the existence of a direct link between SEP and performance. Bandura and Locke (2003) also report nine meta-analyses that indicate that SEP influences, directly or indirectly, the motivation and performance at work (see also Bandura 1997Bandura , 2004Ivancevich et al 2011;Luthans et al 2007;Sadri and Robertson 1993;Oude Groote Beverborg et al 2015). Bandura (1982a) also states that SEP influences the motivation and performance of an employee in three manners: by determining the level of objectives that the individual sets for himself (a high SEP leads to high objectives), by characterizing the intensity of the efforts deployed (high SEP due to the fact that the individual is confident of his success possibility) and by relying on perseverance.…”
Section: In the Professional Fieldmentioning
confidence: 99%
“…Stajkovic and Luthans (1998) meta-analysis, which focuses on professional performances, shows the existence of a direct link between SEP and performance. Bandura and Locke (2003) also report nine meta-analyses that indicate that SEP influences, directly or indirectly, the motivation and performance at work (see also Bandura 1997Bandura , 2004Ivancevich et al 2011;Luthans et al 2007;Sadri and Robertson 1993;Oude Groote Beverborg et al 2015). Bandura (1982a) also states that SEP influences the motivation and performance of an employee in three manners: by determining the level of objectives that the individual sets for himself (a high SEP leads to high objectives), by characterizing the intensity of the efforts deployed (high SEP due to the fact that the individual is confident of his success possibility) and by relying on perseverance.…”
Section: In the Professional Fieldmentioning
confidence: 99%
“…Other methods for exploring change may yield additional insights, particularly if data are available for more than two years. These include latent difference score modeling (McArdle & Hamagami, 2001;Oude Groote Beverborg, Sleegers, Endedijk, & van Veen, 2015) and latent growth curve modeling (e.g., McArdle & Epstein, 1987). Such models would allow for the investigation of several aspects of a school's change in climate over time, including the average change across all schools, the variability in the amount of change across schools, and the extent to which change is associated with the initial school status.…”
Section: Discussionmentioning
confidence: 99%
“…Expectation-consistent person information is suggested to result in stereotype-based processing and judgments that are biased through activated expectations, while expectation-inconsistent information should result in information-integrating processing and more accurate judgments. Research has already demonstrated that teachers as well as pre-service teachers rely on stereotypical expectations when it comes to the academic judgment of negatively stereotyped students such as racial or ethnic minority students McCombs and Gay 1988;Parks and Kennedy 2007). This research implies that academic achievement judgments are not biased through race or ethnicity per se, but rather that students who confirm negative stereotypical expectations were judged according to the stereotype while students who did not behave stereotypically did not experience disadvantages because of their race or ethnicity Neal et al 2003).…”
Section: Theoretical Backgroundmentioning
confidence: 93%
“…This implies that teacher education programs should focus on judgment formation processes: initiating self-reflective processes among pre-service teachers, for example by providing them with knowledge about biases in social judgment formation and how they could prevent them, might ensure the fair treatment of all students. Engagement in reflection has been found to have a positive influence on self-efficacy beliefs (Oude Groote Beverborg et al 2015). In this case, self-reflection might boost teachers' expectation to be efficacious in judging students fairly on merits and not on appearance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation